Innocent bystanders: how foreign uncertainty shocks harm exporters - Daria Taglioni; Veronika Zavacka (European Central Bank (ECB), 2013)
The failure of trade economists to anticipate the extreme drop in trade post Lehman Brothers bankruptcy suggests that the behavior of trade in exceptional circumstances may still be poorly understood. This paper explores whether uncertainty shocks have explanatory power for movements in trade. VAR estimations on United States data suggest that domestic uncertainty is a strong predictor of movements in imports, but has little effect on exports. Guided by these results, the paper estimates a bilateral model with focus on the impact of importer uncertainty on foreign suppliers. It finds that there is a strong negative relationship between uncertainty and trade and that this relationship is non-linear. Uncertainty matters most when its levels are exceptionally high. The paper does not find evidence of learning from past turmoils, suggesting that prior experience with major uncertainty shocks does not reduce the effect on trade. In line with the expectations, the negative effect of uncertainty shocks on trade is higher for trade relationships more intensive in durable goods. Surprisingly, however, the effect of durability is non-linear. Supply chain considerations or the possibility that the relationships with the highest durability lead to important compositional effects may have a bearing on the results. The results are robust to excluding the post Lehman shock, suggesting that the trade response during the 2008-2009 crisis has been similar to past uncertainty events.
Keywords: F02; F10; G01; 330; exporters; international trade; uncertainty shocks